The prognostic significance of the lymph node ratio in oral cancer differs for anatomical subsites. Issue 5 (May 2020) - Moratin, J.; Metzger, Karl; Kansy, K.; Ristow, O.; Engel, M.; Hoffmann, J.; Flechtenmacher, C.; Freier, K.; Freudlsperger, C.; Horn, D.
Abstract: The aim of this study was to validate the prognostic significance of the lymph node ratio (LNR) in patients suffering from oral squamous cell carcinoma in regard to different anatomical subsites. A cohort of 430 patients was investigated to determine the rates of primary metastasis and local and regional disease recurrence. Correlation analysis of the LNR with relevant clinical and pathological parameters was performed. Receiver operating characteristic (ROC) curve analysis was conducted to evaluate the prognostic impact for different subsites. Significantly differing rates of primary metastasis and loco-regional disease recurrence were found for cancer of different anatomical subsites of the head and neck. Furthermore, ROC curve analysis suggested that LNR has prognostic relevance in subsets of cancer (tongue, P < 0.001; alveolar process, P = 0.04; maxilla, P = 0.03; buccal mucosa, P = 0.02). The LNR of cancer located in the soft palate ( P = 0.6) and floor of the mouth ( P = 0.11) showed little or no association with the clinical outcome. There is the need for a more sensitive consideration of the LNR as a factor in the assessment of risk and the treatment decision, as the anatomical subsite plays a crucial role in its impact on the clinical outcome.